Angiogenesis, haemostasis and cancer: new paradigms and old concerns - Duarte, Maria (2007)
Neovascularization is a crucial phenomenon for the continuous growing of neoplastic cells and cancer progression. The growth of new blood vessels from pre-existing vessels (angiogenesis) occurs in several physiological and pathological conditions, including cancer, where it is critical for tumor-cells nutrition. Recently, new remarkable insights regarding angiogenesis and blood coagulation (key events in vascular biology) have been described. The serine protease thrombin, which plays a central role in blood coagulation cascade through its ability to cleave fibrinogen conducting to fibrin clot formation, is also known to be involved in embryogenesis, inflammation, wound healing, through its active role on vascular remodeling. Although the increased knowledge of factors regulating angiogenesis and coagulation led to the understanding that angiogenesis, homeostasis and carcinogenesis are three close team players, little is still known about how these pathways support each other in the process of angiogenesis in vivo. This review summarizes current understanding of blood coagulation cascade role in conducting angiogenesis and tumor progression, as well as provides an overview of the emerging anti-angiogenic and anti-coagulation therapies inducing tumor regression.